Implementasi Program Siaga Gawat Darurat Ibu Hamil (Sigar Bumi) di Kota Magelang: Studi Kualitatif Deskriptif - Aini, Nurul; Fitri Mutmainah, Nur (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study aims to describe and analyze the implementation of the Pregnant Women Emergency Alert (SIGAR BUMI) program in Magelang City using a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and analyzed using George C. Edward III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure. The findings show that communication has been effective through face-to-face socialization and the use of digital media, although limited digital literacy remains a challenge. In terms of resources, the number of medical staff, especially midwives and call center officers, is not proportional to the number of pregnant women in Magelang City (1,225 in 2023), indicating the need for additional personnel for each shift. The disposition of implementers demonstrated responsive and friendly attitudes, highly appreciated by patients due to the quick response in emergency cases. Bureaucratic structure supports the implementation through SOPs and inter-agency coordination, although authority remains limited to pre-hospital care. The study implies the importance of strengthening human resources, providing maternal-specialized ambulances, and adopting adaptive communication strategies to optimize the program. Policy recommendations are directed at increasing local government support in terms of budget and health personnel to ensure program sustainability.